Online Learning Preferences And Motivational Impact In Learning English During Covid-19 (International Online Journal of Language, Communication, and Humanities (INSANIAH), 2023)
The increase number of Covid-19 outbreaks has profoundly changed our education system. From ordinary face-to-face learning, the educators need to find new alternatives in adapting the students into online learning. Therefore, the objective of this study was to determine the students' motivation to using e-Campus as an online platform in learning the English Language at Universiti Malaysia Kelantan using the questionnaires adapted from the ARCS Model of Motivation. 161 English language learners from various levels of classes participated in this study using simple random sampling. Data from the questionnaires consisting of 20 items on an observation checklist were collected, analysed, and supplemented using descriptive statistical analysis of students’ responses from questionnaires. The findings indicated that 68% of the students exhibited positive feedback towards the use of e-Campus as an online platform when learning the English language during the pandemic period. This study also suggested a need to improve students' experiences of using e-Campus as an online learning platform to implement online teaching and learning successfully. The outcome is believed to be valuable for educational authorities in planning, developing, and implementing measures to address possible challenges faced by students when using e-Campus as their main alternative in online learning. It is hoped that more future research should be carried out so that the students who are currently using e-Campus as their online learning platform will be able to learn and comprehend their language learning despite the challenges.